Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3171/2014.7.spine131087
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurements of C-2 in patients with atlas assimilation

Abstract: Object The object of this study was to evaluate the radiographic characteristics of C-2 using multiplanar CT measurements for anchor screw placement in patients with C-1 assimilation (C1A). Insertion of a C-2 pedicle screw in the setting of C1A is relatively difficult and technically demanding, and there has been no report about the optimal sizes of the pedicles and laminae of C-2 for screw placement in C1A. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
2
12
2
Order By: Relevance
“…Our measurements showed that the mean C2 pedicle thickness in OA was 3.5 mm and significantly smaller than in the control group (mean 6.4 mm), and also less than that in the Aoyama et al 32 study (mean 5.2 mm). Smith et al 33 reported the mean pedicle thickness was 5.8 mm in normal people, which was close to the value in our study and yet far smaller than that in the Aoyama et al 32 result (mean 7.2 mm). With pedicle thickness of 4 mm, approximately 13.7% of patients may receive pedicle screw fixation at C2 (Table 3 ).…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…Our measurements showed that the mean C2 pedicle thickness in OA was 3.5 mm and significantly smaller than in the control group (mean 6.4 mm), and also less than that in the Aoyama et al 32 study (mean 5.2 mm). Smith et al 33 reported the mean pedicle thickness was 5.8 mm in normal people, which was close to the value in our study and yet far smaller than that in the Aoyama et al 32 result (mean 7.2 mm). With pedicle thickness of 4 mm, approximately 13.7% of patients may receive pedicle screw fixation at C2 (Table 3 ).…”
Section: Discussioncontrasting
confidence: 62%
“… 33 , 34 Based on this requirement, the percentages dropped to only 1.4% of our patients who may receive pedicle screw fixation at C2 levels. According to Aoyama et al 32 results, there were no pedicle thickness less than 5 mm in the right side, and yet in our study 87.7% and 93.2% of pedicle thicknesses in the right and left side, respectively, were smaller than 5 mm. Smith et at 33 demonstrated the mean pedicle angle was 43.9°, which was close to the normal population (mean 39.5°) and bigger the angle in the patients with OA (mean 36.9°) in our study.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations